Ukraine : First Review Under the Stand-By Arrangement, Requests for Waivers of Nonobservance of Performance Criteria, and Rephasing of Purchases Under the Arrangement; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Ukraine's economic downturn has been sharper than originally envisaged, mostly reflecting the deterioration of the external environment. The staff report examines Ukraine's first review under the Stand-By Arrangement, requests for Waivers of Nonobservance of Performance Criteria, and Rephasing of Purchases Under the Arrangement. A flexible exchange rate policy, supported by base money targets and a transparent intervention strategy, remains a key component of the program. Given balance sheet effects associated with unhedged foreign currency borrowing, the central bank stands ready to take action to avoid excessive exchange rate depreciation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet